2019
DOI: 10.1007/s11469-019-00139-5
|View full text |Cite
|
Sign up to set email alerts
|

Histrionic Personality, Narcissistic Personality, and Problematic Social Media Use: Testing of a New Hypothetical Model

Abstract: In the present study, a hypothetical model examining the relationships between histrionic personality belief, need for social approval, desire for being liked, social media disorder, and narcissistic personality belief was proposed and tested. The effect of histrionic personality belief on the need for social approval and desire for being liked was tested first. Then the effect of the need for social approval and desire for being liked on social media addiction were tested. Finally, the effect of social media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 93 publications
(95 reference statements)
0
10
0
3
Order By: Relevance
“…Previous studies revealed that narcissism was positively and significantly associated with Facebook usage (Ryan & Xenos, 2011), internet addiction (Ekşi, 2012), and problematic smartphone use (Servidio et al, 2021). Additionally, adolescents' desire to be liked and PSMU were found to be positively related (Savci et al, 2021). Furthermore, psychopathy was found to be positively linked with PSMU (Demircioğlu & Göncü-Köse, 2021).…”
Section: Effects Of the Dt Personality Traits On Psmu And Cyberbullyingmentioning
confidence: 89%
“…Previous studies revealed that narcissism was positively and significantly associated with Facebook usage (Ryan & Xenos, 2011), internet addiction (Ekşi, 2012), and problematic smartphone use (Servidio et al, 2021). Additionally, adolescents' desire to be liked and PSMU were found to be positively related (Savci et al, 2021). Furthermore, psychopathy was found to be positively linked with PSMU (Demircioğlu & Göncü-Köse, 2021).…”
Section: Effects Of the Dt Personality Traits On Psmu And Cyberbullyingmentioning
confidence: 89%
“…Unlike in the past, today’s human relationships are established in great detail and recorded on social media. Although these networks help increase organizational performance, organization members with a histrionic personality seek attention and approval (Savci et al, 2019) and deliberately reveal their ties on social media to provoke envy. This study has shown that envy among members can exacerbate the negative effects of guanxi.…”
Section: Discussionmentioning
confidence: 99%
“…‫و"‬ ‫ومولياني"،‬ ‫اهاردجو‬ ‫و"ر‬ ‫وآخرون،‬ ‫ي"‬ ‫"جيرواس‬ ‫اسات‬ ‫در‬ ‫نتائج‬ ‫مع‬ ‫وتختلف‬ ‫وآخرون‬ ‫اد"‬ ‫نژ‬ ‫علوي‬ ( ‫ايلووسكايا"‬ ‫و"بر‬ ‫و"ليووما"،‬ ‫اف"،‬ ‫ومارجر‬ ‫ايلووسكايا‬ ‫و"بر‬ ‫وآخرون،‬ ‫"اندرسون"‬ ‫اسات‬ ‫در‬ ‫نتائج‬ ً ‫وأيضا‬ .) ‫العالية‬ ‫املستويات‬ ‫بين‬ ‫واضحة‬ ‫عالقة‬ ‫وجود‬ ‫بمجملها‬ ‫اكدت‬ ‫والتي‬ ‫وآخرون،‬ ‫و"ساوجي"‬ ‫وفيوراوانتي"،‬ ‫و"كاسل‬ ‫وآخرون،‬ ‫و"هاوك"‬ ‫وآخرون،‬ ‫واإل‬ ‫(العظمة)‬ ‫سمة‬ ‫من‬ ‫دمان‬ ‫ع‬ ‫اال‬ ‫التواصل‬ ‫شبكات‬ ‫لى‬ ‫جتماع‬ ‫ي‬ ( Andreassen, Pallesen and Griffiths, 2017;Brailovskaia and Margraf, 2017;Liu and Ma,2018;Brailovskaia et al, 2018;Hawk et al,2019;Casale and Fioravanti,2018;Savci et Xiuqin et al, 2010;Fisoun et al, 2012;Yan, Li and Sui, 2013;Dong et al, 2013 ) .…”
Section: ‫البحث:‬ ‫مجتمع‬unclassified